'A Strong International Spirit': The Influence of Internationalism on the Women's Co-operative Guild. (14th April 2020) - Hellawell, Sarah
Abstract: This article explores the internationalism of the Women's Co-operative Guild (WCG) during the interwar years. Drawing on the records of the national and international Guild, alongside the minute books of a local branch based in Darlington, County Durham, it positions the WCG in the vibrant political culture in Britain during the 1920s and 1930s. Building on recent literature that has sought to examine the phenomenon of interwar internationalism, this article sheds light on an organization that represented the interests of working-class women. Internationalist in outlook, the association demonstrates how internationalist ideals played out on a day-to-day basis. The article demonstrates that the WCG played a unique and complementary role within both the British and international women's movements.